Association between wrist ratio and carpal tunnel syndrome: Effect modification by body mass index. Issue 6 (14th June 2017) - Thiese, Matthew S.; Merryweather, Andrew; Koric, Alzina; Ott, Ulrike; Wood, Eric M.; Kapellusch, Jay; Foster, James; Garg, Arun; Deckow‐Schaefer, Gwen; Tomich, Suzanna; Kendall, Richard; Drury, David L.; et al.
ABSTRACT: Introduction: Previous studies have reported higher wrist ratios (WR) related to carpal tunnel syndrome (CTS) but have not assessed effect modification by obesity and may have inadequately controlled for confounders. Methods: Baseline data of a multicenter prospective cohort study were analyzed. CTS was defined by nerve conduction study (NCS) criteria and symptoms. Results: Among the 1, 206 participants, a square‐shaped wrist was associated with CTS after controlling for confounders (prevalence ratio = 2.27; 95% confidence interval [95% CI], 1.33–3.86). Body mass index (BMI) was a strong effect modifier on the relationship between WR and both CTS and abnormal NCS results, with normal weight strata of rectangular versus square wrists = 8.18 (95% CI, 1.63–49.96) and 7.12 (95% CI, 2.19–23.16), respectively. Discussion: A square wrist is significantly associated with CTS after controlling for confounders. Effect modification by high BMI masked the eightfold magnitude adjusted relationship seen between WR and CTS among normal weight participants. Muscle Nerve 56 : 1047–1053, 2017